Energy Efficiency and Carbon-Neutral Knowledge, Attitudes and Perception (KAP) across the Campuses of Lagos State University (LASU), Nigeria - Fatai Olakunle Ogundele; Ibiyemi Ibilola Olatunji-Bello; Adejuwon Adewale Adeneye (Journal of Sustainability Perspectives, 2025)
This study investigated students’ awareness, participation, and commitment to sustainability initiatives across the four campuses of Lagos State University (LASU), Ojo, Ikeja, Epe, and Badagry. Data were collected from 214 randomly selected students. The data obtained were analyzed using simple percentages, tables, Pearson correlation, and One-Way ANOVA. The results obtained revealed that 49.1% of the respondents demonstrated high awareness of sustainability initiatives, with Badagry campus recording the highest awareness at 95.5%, and Ikeja the lowest at 35.6%. Furthermore, 63.1% of students indicated familiarity with LASU’s sustainability programmes, reflecting a moderate level of institutional visibility, while 48.1% rated the visibility of these efforts as high, again with Badagry leading at 95.5%. Despite these levels of awareness, only 26.6% of students strongly agreed that LASU is committed to sustainability. Among campuses, Badagry (50.0%) and Ikeja (42.2%) showed the strongest perceptions of institutional commitment. Opinions on LASU’s energy initiatives were mixed: 54.2% rated them as somewhat effective, 28.5% as very effective, and 39.3% believed the efforts were insufficient. Statistical analysis showed positive correlations between awareness and energy-saving behavior (r = 0.224, p = 0.001), as well as between awareness and intentions for future participation (r = 0.174, p = 0.011). Adoption of energy-saving behaviors varied significantly across campuses (F = 10.841, p = 0.000), while intentions to participate in future initiatives did not show significant differences (F = 2.023, p = 0.112). The result generally revealed that LASU students exhibited moderate to high levels of engagement with sustainability initiatives. The notable variations in awareness, perception, and participation across campuses, especially between Badagry and others, highlight the need for tailored, campus-specific strategies to ensure more balanced and widespread adoption of sustainable practices.